Kekerasan Fisik dan Verbal pada Perawat yang Bekerja di Rumah Sakit di Aceh - Safrina Edayani; Rahmat Muhazir (Jurnal Ners, 2025)
Violence against nurses refers to incidents in which nurses are harassed, threatened, or assaulted in relation to their professional duties, including during commutes to and from work, impacting their safety, well-being, and health. Alleged acts of violence against nurses have been committed by various members of society, ranging from ordinary citizens to local government officials. The most commonly reported forms of violence include verbal abuse (54.3%), bullying (28.6%), physical assault and threats (each 19%), sexual harassment (11.4%), and other forms of abuse (8.6%). The majority of perpetrators were identified as patients' family members (63.5%). Such violence affects not only the physical health of nurses but also their mental well-being, potentially reducing their productivity, straining relationships with colleagues, lowering job satisfaction, and increasing turnover rates—all of which negatively impact patients, nurses, and healthcare institutions. This study aimed to explore in depth the physical and verbal violence experienced by nurses working in hospitals across Aceh. A qualitative phenomenological design was employed. Data were collected through interviews and observations, and analyzed using content analysis. The findings revealed six main themes: forms of violence, perpetrators, contributing factors, nurses’ responses to violence, coping mechanisms, and the support systems available during violent incidents. Keywords: Physical Violence, Verbal Violence, Nurses